The Effects of Emotional Intelligence, Self-Efficacy, and Online Learning on College Stress, with Motivation as an Intervening Variable (Study on Accounting Study Program Students at Muhammadiyah University of Sidoarjo) - Cynthia Tamara Surya; Sigit Hermawan; Nurasik Nurasik; Ruci Arizanda Rahayu (FEB Universitas Sultan Ageng Tirtayasa, 2023)
Investigating the direct effects of emotional intelligence, self-efficacy, and online learning on accounting students' college stress. It also seeks to understand the role indirectly through motivation as an intervening variable in this relationship. This study uses a quantitative methodology and uses primary data. Respondents are given questionnaires to complete to collect data. This study population consisted of accounting students from the 2018 academic year. Probability sampling with simple random sampling is used as the sampling technique. The research sample, which was determined by the Slovin formula, consisted of 149 participants from Sidoarjo’s Muhammadiyah University's Accounting Program. The structural equation model (SEM) approach to data analysis was applied, and the tool SmartPLS version 3.2.9 was used. Data analysis is done using the stages of the outer and inner models. According to the study's findings, emotional intelligence and self-efficacy have no discernible influence on college stress. On the other hand, college stress is significantly impacted by motivation and online learning. Emotional intelligence, self-efficacy, and online learning also have a big impact on motivation. It has been demonstrated to attenuate the effects of emotional intelligence, self-efficacy, and online learning on college stress.